Levels of agreement between clinical examination and transabdominal ultrasound evaluation of fetal head position in the second stage of labor. (1st February 2016) - Costa, Ana Gomes da; Barros, Joana Goulão; Clode, Nuno; Graça, Luís Mendes da
Abstract: Aim : To compare transvaginal digital examination performed by residents and attending physicians to transabdominal suprapubic ultrasound in the evaluation of fetal head position in the second stage of labor. Methods : A prospective study was conducted at a tertiary center and included pregnant women at term, with normal singleton cephalic presentation fetuses. All patients had ruptured membranes and were evaluated during the second stage of labor. Fetal head position was assessed consecutively by two clinicians (one resident and one attending physician). Afterwards, transabdominal suprapubic ultrasound was performed by another observer. Examiners were blinded to each other's findings. Cohen's kappa test was used to assess the degree of agreement between the evaluation methods. Results : One-hundred sixty-one women were included. Transvaginal examination was consistent with the ultrasound in 45.0% of cases (95% CI: 37–53%) when the examination was performed by residents ( k  = 0.349) and in 67% (95% CI: 60–74%) if the attending physician carried out the evaluation ( k  = 0.604). When considering only the anterior positions, the Cohen's kappa test was 0.426 and 0.709, respectively. Conclusion : Transabdominal suprapubic ultrasound improved the accuracy of the evaluation of fetal head position, namely when transvaginal digital examination was performed by residents. This may be important especially when instrumental deliveries are considered.